Analysis of the Level of Financial Literacy among South African Undergraduate Students - Oseifuah, Emmanuel K. (Journal of Economics and Behavioral Studies, 2014)
The purpose of the study was twofold: to examine the relationship between financial literacy and demographic and other socioeconomic factors of a sample of undergraduate students; and to evaluate how undergraduate studentsâ€™ financial knowledge correlate with their attitude and behavior towards personal finance issues. A structured questionnaire was used to collect data and logistic regression and Chi-Square statistical procedures were employed to analyse the data using the Statistical Package for Social Scientists (SPSS) software. Overall, this pilot study reveals that Bachelor of Commerce(Accounting) students at the University of Venda are not as financially literate as expected, confirming the findings of similar studies conducted on South African university students (KotzÃ¨ and Smidt, 2008). There is therefore the necessity to review the academic curriculum in the Bachelor of Commerce programme to include money management course. Furthermore, with more South African university students likely to depend on bank loans to finance their education, it is recommended that financial literacy be made a compulsory course in all undergraduate programmes in South African universities.